Thermal Convexity of Tubular Heat Exchangers in Steady State - Abdelghani-Idrissi, M.A.; Seguin, D.; Vernières, L.; Mouhab, N. (Journal of Advanced Thermal Science Research, 2015)
This paper deals with the thermal convexity of heat exchangers in steady state: (Th,c(x)=γh,c(x)Tc,in+(1- γh,c(x))Th,in with 0 ≤ γh,c(x) ≤ 1). This method assesses the spatial distribution of the thermal convexity factors of both fluids along a tubular heat exchanger in counter-current flow and co-current flow arrangement. Analytical expressions of the thermal convexity coefficients are in exponential form. According to the flow configuration two linear functions are proposed for the hot and the cold fluid. The slope of these two functions corresponds to the exponential factor. The estimations of the exponential factor thanks to the steady state convexity coefficient profile provide results that are in good agreement with those obtained from correlations.